Implementasi Pancasila dan Civil Societ di Era Informasi - Aditya Sitorus, Fauzi; Habibah Tarigan, Alya (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the implementation of Pancasila values ​​in the information era and identify the role of civil society in supporting the strengthening of these values. In addition, this study also aims to reveal the obstacles faced in the implementation of Pancasila amidst the development of information technology and formulate effective strategies to integrate Pancasila values ​​with the dynamics of digitalization in order to realize a just, harmonious, and dignified society. It can be concluded that the implementation of Pancasila values ​​in the information era is very important to maintain national integrity and strengthen social cohesion amidst the flow of globalization. Pancasila, as the foundation of the state, remains relevant and must be implemented consistently to ensure that technological developments do not erode national values ​​and national morality. The information era presents challenges in the form of the spread of hoaxes, social polarization, and threats to individual privacy, which require a wise response based on the principles of Pancasila. The implementation of Pancasila values ​​in the digital era must be supported by various parties, including the government, society, and the private sector. The government plays an important role in creating policies that ensure technology is used for the benefit of society, and protect the basic rights of every individual, especially in terms of privacy and access to information. Society also needs to develop digital literacy that prioritizes media ethics and social awareness, so that technology can be used to strengthen the sense of unity and social justice in Indonesia.